(untitled) (Development Service Industry Management, 2025)
The article considers the implementation of the HACCP risk analysis and critical control point system in the technological process of restaurant enterprises, with an emphasis on the features and problems that arise in conditions of limited resources and the specifics of small and medium-sized businesses. It analyzes how HACCP standards can be adapted for the domestic restaurant sector, taking into account the flexibility of the menu, individual recipes and frequent changes in the product range. The article emphasizes the need for a comprehensive approach that includes organizational, personnel, technical and economic aspects. Particular attention is paid to the key stages of HACCP implementation, such as raw material acceptance, product storage, technological processing and serving of dishes. At each of these stages, critical control points are identified that must be carefully monitored to minimize the risks of food contamination and ensure safety. Control methods are considered in detail, including temperature checks, separate storage of products and the sanitary condition of equipment. The article also provides recommendations for the effective organization of production in domestic restaurant enterprises, including on the basis of available means and methods. Ways to solve the problem of lack of resources for the full implementation of the HACCP system are described. The conclusion of the article formulates the authors’ opinion on the importance of HACCP as a strategic tool for improving food safety, consumer confidence and competitiveness of restaurant enterprises. The prospects for using digital technologies to simplify control and optimize work processes, as well as the integration of the HACCP system with the concepts of sustainable development in the restaurant industry are considered.